Personal Hygiene, Environmental Sanitation and Hepatitis A Infections in Universitas Jember - Dian Septivita; Isa Ma’rufi; Farida Wahyu Ningtyias (Humanistic Network for Science and Technology (HNST), 2018)
Hepatitis A is a disease caused by type A hepatitis virus that attacks human liver cells. The disease is closely related to the lack of clean water, inadequate sanitation and poor personal hygiene. Hepatitis A can lead to the incidence of widespread public health problems and cause outbreaks. The purpose of this study was to analyze the effect of personal hygiene and environmental sanitation on the incidence of hepatitis A at Universitas Jember. The researcher used observational analytics research design with case-control approach. A total of 92 respondent consisting of case and control respondents was taken as samples. Case sample selected by using simple random sampling, and control sample selected by using purposive sampling. The data were analyzed by using Chi-square test. The results showed that personal hygiene had an effect on the incidence of hepatitis A with p-value of 0.000, while environmental sanitation had no effect with p-value of 0.402. There is a need to enhance the active role of health workers in providing health promotion means in schools, such as routine health counseling to improve students' knowledge about hepatitis A and the way to prevent the disease through behavior improvement. Keywords: hepatitis A virus; personal hygiene; sanitation